PELATIHAN PENYUSUNAN PROPOSAL ART BASED RESEARCH (ABR) DENGAN BERORIENTASI PADA PENYELESAIAN STUDI S-1 JALUR PENCIPTAAN KARYA KREATIF - Nugroho, Rudi Adi; Sumiyadi; Kusumah, Encep; Iskandar, Denny; Rizkyanfi, Mochamad Whilky; Puspita, Yulia (Universitas Negeri Surabaya, 2025)
The path of creative work creation as an alternative to completing undergraduate studies in the field of Indonesian Language and Literature Education has not been widely implemented on other campuses. Many Indonesian Language and Literature Education Study Programs on campus are still preparing this scheme as an alternative that students can choose to complete their undergraduate studies. This training aims to share good practices that have been carried out in PBSI UPI Study Program on the application of research with the art-based research method. This training was attended by participants who were final year students in the Language and Literature Education Study Program at Ganesa University of Education. The training has been carried out synchronously and asynchronously. Synchronous activities are carried out using Zoom Meeting. Asynchronous activities are carried out by participants independently using indirect coordination and assistance through google form and google drive. The results achieved from this activity, participants have understood the basic concepts of art-based research methods in the field of Indonesian Language and Literature Education. Regarding the application of these concepts, the achievements of the participants were quite varied from those that were good to those that were still not fully able to apply the concepts that had been given.